Aktivitas Antihiperglikemia Infusa Daun Sambung Nyawa (Gynura Procumbens) dengan Metode Toleransi Glukosa pada Mencit Jantan (Mus Musculus): Antihyperglycemic Activities of Sambung Nyawa Leaves (Gynura Procumbens) Infusion using a Glucose Tolerance Method in Male Mice (Mus Musculus) - Ridhotulloh, Yusuf Isro; Rijai, Laode; Mus, Nurul Muhlisa; Arifuddin, M.; Ibrahim, Arsyik; Ahmad, Islamudin; Herman, Herman; Hikmawan, Baso Didik; Junaidin, Junaidin; Febrina, Lizma; Faisal, Muhammad; Rusman, Arman; Riki, Riki; Almeida, Maria; Bone, Mahfuzun; Arifian, Hanggara; Samsul, Erwin (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Hyperglycemia is a condition where blood sugar increases significantly which can lead to diabetes mellitus. Sambung Nyawa (Gynura Procumbens) leaves are a plant that is empirically believed to reduce hyperglycemia and has been scientifically proven based on several studies, however there has been no research that provides information about sembung nyawa leaves in infusion form. This study aims to determine the content of secondary metabolites in the infusion of the leaves of Gynura Procumbens and its antihyperglycemia activity in male males. This study consisted of phytochemical and antihyperglycemia screening using a tolerance method induced by glucose monohydrate at a dose of 2g/kgBW. The test group consisted of a negative control group (Na CMC 1%), a positif group (Glibenclamide), and 3 groups of sambung nyawa leaf infusion (5%, 10%, 15%). The results of the research showed that the infusion of sembung nyawa leaves contained secondary metabolites, namely tannins, phenolics, flavonoids and saponins. The effect of reducing blood sugar levels in test animals showed a significant reduction (0.00<0.05) at a 10% concentration infusion compared to the negative control and not significant to the positive control. The conclusion shows that the infusion of sambung nyawa leaves has an antihyperglycemic effect. Keywords: Antihyperglycemic, Sambung Nyawa Leaves, Glucose Monohydrate Abstrak Hiperglikemia merupakan kondisi peningkatan gula darah yang cukup signifikan yang akan berubah menjadi kondisi diabetes mellitus. Daun sambung nyawa (Gynura Procumbens) merupakan tumbuhan yang dipercaya secara empiris menurunkan hiperglikemia dan terbukti secara ilmiah berdasarkan beberapa penelitian dalam bentuk ekstrak. Penelitian ini bertujuan mengetahui kandungan metabolit sekunder pada infusa daun sambung nyawa dan aktivitas antihiperglikemia pada mencit jantan. Penelitian ini terdiri dari skrining fitokimia dan antihiperglikemia menggunakan metode toleransi yang dinduksi glukosa monohidrat dengan dosis 2g/kgBB. Kelompok uji terdiri dari kelompok kontrol negatif (Na CMC 1%), positif (Glibenklamid), dan 3 kelompok infusa daun sembung nyawa (5%, 10%, 15%). Hasil penelitian menunjukkan infusa daun sambung nyawa mengandung metabolit sekunder yaitu tanin, fenolik, flavonoid dan saponin. Efek penurunan kadar gula darah pada hewan uji menunjukkan penurunan yang signifikan (0,00<0,05) pada infusa konsentrasi 10% dibandingkan dengan kontrol negatif dan tidak signifikan terhadap kontrol positif. Kesimpulan menunjukkan bahwa infusa daun sambung nyawa mempunyai efek antihiperglikemia. Kata Kunci: Antihiperglikemia, Daun Sambung Nyawa, Glukosa Monohidrat